Disponibilidad de antibióticos en tiendas de Guatemala - Purificación Moreno; Celia Cordón; Brooke M Ramay; Laura Grajeda; Guy H Palmer; Maria Renee Lopez; Marinees Morales; Karen Sosa; Alejandro Cerón; Douglas R Call (Instituto Nacional de Salud Pública, 2021)
No disponible